Impact of high intensity exercise on muscle morphology in EAE rats - Wens, I; Dalgas, U; Verboven, K; Kosten, L; Stevens, A; Hens, N; Eijnde, B O (Physiological research, 2015)
The impact of high-intensity exercise on disease progression and muscle contractile properties in experimental autoimmune encephalomyelitis (EAE) remains unclear. Control (CON) and EAE rats were divided into sedentary and exercise groups. Before onset (experiment 1, n=40) and after hindquarter paralysis (experiment 2, n=40), isokinetic foot extensor strength, cross sectional area (CSA) of tibialis anterior (TA), extensor digitorum longus (EDL) and soleus (SOL) and brain-derived neurotrophic factor (BDNF) levels were assessed. EAE reduced muscle fiber CSA of TA, EDL and SOL. In general, exercise was not able to affect CSA, whereas it delayed hindquarter paralysis peak. CON muscle work peaked and declined, while it remained stable in EAE. BDNF-responses were not affected by EAE or exercise. In conclusion, EAE affected CSA-properties of TA, EDL and SOL, which could, partly, explain the absence of peak work during isokinetic muscle performance in EAE-animals. However, exercise was not able to prevent muscle fiber atrophy.
Keywords: Animals; potkani inbrední LEW; Eating; Female; ženské pohlaví; svalová síla; kondiční příprava zvířat; přijímání potravy; Muscle Strength; encefalomyelitida autoimunitní experimentální; kosterní svalová vlákna; tělesná hmotnost; Muscle Fibers, Skeletal; progrese nemoci; Disease Progression; Brain-Derived Neurotrophic Factor; Body Weight; Physical Conditioning, Animal; mozkový neurotrofický faktor; Encephalomyelitis, Autoimmune, Experimental; Random Allocation; zvířata; Rats, Inbred Lew; náhodné rozdělení